Penguatan Etika Pemerintahan sebagai Upaya Meningkatkan Kinerja Aparatur Pemerintahan - Afrijal, Afrijal; Helmi, Helmi; Latif, Ikhwan Rahmatika; Usman, Bustami (Jurnal Pemerintahan dan Politik, 2023)
Accelerating government ethics in bureaucracy is a very important thing for every government apparatus to realize. As a government administrator, you must be able to actualize ethical values in providing services to the community. The aim of this research is to examine and explain how to strengthe government ethical values as an effort to improve the performance of government officials. The method used in this writing is a qualitative method with a literature review study approach. The results of the discussion in this paper show that strengthening government ethics can be realized by internalizing Pancasila values for government officials. Pancasila, as a state ideology and also as a guideline for attitudes and behavior, needs to be synergized by the apparatus in the form of services to the community. Apart from that, it is urgent to implement bureaucratic culture reform by the government as the embodiment of professional and qualified bureaucrats.